Albania : First Review Under the Third Annual Arrangement Under the Poverty Reduction and Growth Facility and Request for Waiver of Performance Criteria. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2001)
Executive Directors commended the authorities for their policies to maintain macroeconomic stability, which had resulted in favorable growth performance and zero inflation, and welcomed improvements in tax collection and encouraged the authorities to continue with their efforts to strengthen tax administration. The authorities are urged to proceed rapidly with structural reforms, in particular by improving governance further to ensure sustained growth and poverty reduction. Macroeconomic data, although adequate for program monitoring, continue to suffer from serious deficiencies, especially in the real sector.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet